A STUDY ON KNOWLEDGE, ATTITUDE, AND PERFORMANCE OF NURSES REGARDING HAND HYGIENE - AKHTER , HS; YOUSAF , S; JABEEN, S; NAWA, B (Biological and Clinical Sciences Research Journal, 2024)
Hand hygiene is a critical component of infection control and patient safety, yet compliance with hand hygiene practices remains a significant challenge, particularly in resource-constrained settings like Pakistan. This study aimed to evaluate the knowledge, attitudes, and practices of nurses regarding hand hygiene in a tertiary care hospital. Methods: A descriptive cross-sectional study was conducted among 106 nurses working in various departments, including surgical, medical, and critical care units. Participants were selected through convenience sampling. Data were collected using a prevalidated structured questionnaire covering demographics, knowledge, attitudes, and practices. The data were analyzed using SPSS version 26, employing descriptive and inferential statistics, with a p-value of <0.05 considered significant. Results: The findings revealed moderate knowledge levels (mean score: 8.3 ± 2.4), with 99.5% of participants understanding the need to remove accessories before scrubbing and 82% recognizing the importance of hand hygiene before taking an ECG. Attitudes were generally positive, with 87% agreeing that hand hygiene prevents nosocomial infections. However, only 42.9% consistently used hand hygiene assessment tools, highlighting gaps in practices. Age and education level significantly influenced knowledge and practices (p < 0.05).Conclusion: While nurses demonstrated adequate knowledge and positive attitudes toward hand hygiene, significant gaps in practices were observed. These findings underscore the need for targeted training programs, improved infrastructure, and institutional support to enhance compliance with hand hygiene protocols. Addressing these challenges is essential to reducing healthcare-associated infections and improving patient outcomes in Pakistan.